Exosome-specific tumor diagnosis via biomedical analysis of exosome-containing microRNA biomarkers. Issue 19 (4th September 2019) - Fan, Zhijin; Yu, Jun; Lin, Jingyan; Liu, Ying; Liao, Yuhui
Abstract : A novel exosome-specific tumor diagnosis strategy was constructed by integrating the rapid magnetic exosome-enrichment platform and the Ru(bpy)3 2+ -polymer amplified electrochemiluminescence (ECL) strategy. Abstract : Exosome-containing microRNAs (exomiRs) can be employed as potential biomarkers for tumor diagnosis and have drawn much attention in the past few years. However, the separation of exosomes and the detection of exomiRs are still inconvenient or even difficult to implement. Thus, it is important to develop a simple, accurate, and reliable strategy for the separation of exosomes and the biomedical analysis of exomiRs. Herein, a novel exosome-specific tumor diagnosis strategy was constructed by integrating the rapid magnetic exosome-enrichment platform and the Ru(bpy)3 2+ -polymer amplified electrochemiluminescence (ECL) strategy. This strategy realized the rapid and efficient capture of tumor-derived exosomes through a biological-affinity identification platform of the EpCAM antibody. The biomedical analysis of exomiRs achieved a preferable specificity and high sensitivity of 10 3 particles. Furthermore, we investigated the performance index for clinical blood samples from tumor patients; the results indicated that the exosome-specific tumor diagnosis strategy readily and consistently responded to exomiRs. These results indicated that the exosome-specific tumor diagnosis strategy provided new opportunities for the sensitive and efficient analysis of tumor-derived exomiRs. This strategy greatly simplified the biomedical analysis process and established the non-destructive detection mode of fluid biopsy for tumors.